Cauchy problem for a class of degenerate kolmogorov-type parabolic equations with nonpositive genus - Ivasyshen, S. D.; Litovchenko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We study the properties of the fundamental solution and establish the correct solvability of the Cauchy problem for a class of degenerate Kolmogorov-type equations with $\{\overrightarrow{p},\overrightarrow{h}\}$-parabolic part with respect to the main group of variables and nonpositive vector genus in the case where the solutions are infinitely differentiable functions and their initial values are generalized functions in the form of Gevrey ultradistributions.